2007
DOI: 10.1007/bf03027563
|View full text |Cite
|
Sign up to set email alerts
|

Influence of corrosion properties on electrochemical migration susceptibility of SnPb solders for PCBs

Abstract: Electrochemical migration is caused by the adsorption of water and the bias voltages between the electrodes or pads which form an electric circuit or in the solders used to connect the parts. This work focused on the elucidation of the mechanisms of electrochemical migration of pure Sn, Sn37Pb, and Sn55Pb solders in electronics. The electrochemical migration behavior was discussed on the basis of the polarization behavior of SnPb solders. After the water drop test, the time to failure decreased with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
(5 reference statements)
0
18
1
Order By: Relevance
“…Yoo and Kim [28] have investigated the influence of varying Pb content on ECM using NaCl and Na 2 SO 4 solutions (all neutral pH conditions). In Na 2 SO 4 , the tendency for ECM is seen to decrease due to passivation of Pb, while in NaCl solution, no significant change in the tendency for ECM is observed when the Pb content is increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoo and Kim [28] have investigated the influence of varying Pb content on ECM using NaCl and Na 2 SO 4 solutions (all neutral pH conditions). In Na 2 SO 4 , the tendency for ECM is seen to decrease due to passivation of Pb, while in NaCl solution, no significant change in the tendency for ECM is observed when the Pb content is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Noh and Jung [1] found that ECM migration is more likely to occur on a glass-epoxy FR-4 (flame resistant-4) PCB than on a polyimide PCB. Yoo and Kim [28] investigated the influence of the corrosion properties on ECM in varying Pb concentrations. Sample preparation was done by applying a solder paste of varying Pb content onto a silicon wafer and passing it through a reflow oven.…”
mentioning
confidence: 99%
“…This was ascribed to that a passive layer on Sn surface could be formed in NaCl solution, but not for Pb. Yoo et al 62,67 also found that the time-to-failure of Sn-Pb solder alloys decreased with increasing Pb content in chloridecontaining solution.…”
mentioning
confidence: 94%
“…Lee et al and Yoo et al [60][61][62]67 performed respectively a series of ECM experiments of Pb, Sn and Sn-Pb solder alloys in sulfate-containing solution. They found that the time-to-failure increased with increasing Pb content, indicating that the addition of Pb increased the ECM resistance of Sn-Pb solder alloys in sulfate-containing solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation